Evaluation of four herbal plants and effects of a selected herbal plant Andrographis paniculata (Burm.f.) wall. ex nees as dietary supplement in dairy goats - Hamzah, Siti Fatimah (2016)
Many herbal plants are known to contain one or more chemical compounds that can influence milk production and quality in dairy animals. A study was conducted to examine the potential use of local herbal plant as a natural feed supplement that able to improve digestibility, increase milk production and subsequently improve profitability of dairy farm. The general objectives of this study was to evaluate four local herbal plants based on nutrient composition, antioxidant content, fatty acids profile and in vitro digestibility and to evaluate the effects of selected herbal plants on nutrient digestibility, milk yield and composition of Saanen and Jamnapari goats. Two experiments were conducted in this study. In the first experiment, the nutritive values of Andrographis paniculata, Orthosiphon stamineus, Boreria latifolia and Euphorbia hirta were evaluated. Andrographis paniculata has high value of dry matter (34.56%), ash (14.93%), crude protein (18.13%), gross energy (16.68%), calcium (11.92 mg/L) and low content of ADF (18.80%), and ADL (7.17%). This plant also has high alkaloid (8.50%), saponin (18.73%), and flavonoid (1.25%). Andrographis paniculata has high in vitro DMD and contribute the highest USFA (73.47 g/100g FAME). In addition, the content of linolenic acid (n-3 FA; 36.89g/100g FAME) of Andrographis paniculata was higher than linoleic acid (n-6 FA; 28.93 g/100g FAME). In a subsequent experiment, a feeding trial was conducted using 2 x 2 factorial designs to determine the effect of selected herbal plant (Andrographis paniculata) supplementation on milk yield and its composition in different breed of lactating goats. Thirty-two lactating dairy goats in 4th month of lactation (16 Jamnapari and 16 Saanen) were used. Each breed was randomly allotted into two groups of eight which were control group (unsupplemented) and supplemented group. The diets were formulated in accordance with dairy goat requirements NRC 1981. Feed intake and faecal output and milk yield were recorded and analysed.There was no interaction between dietary treatment group and breed on weight gain, feed intake, nutrient digestibility and milk production (FCM 3.5%). However, there was a significant effect (p<0.05) within dietary treatment group factor and breed factor of parameters measured. Milk production (FCM 3.5%) and milk efficiency of the supplemented group was higher than the control group in both breeds. Goats of Saanen breed had higher milk production and milk efficiency compared to Jamnapari breed. For milk composition, there was interaction between dietary treatment and breed for all milk components except for lactose, phosphorus and calcium contents. Jamnapari goats in the control group had the higher percentage of fat, protein, solid, solid non-fat and total solid than the other groups. Milk from supplemented group in both breed were higher in antioxidant content and low saturated fatty acid compared to the control group. It was concluded that the supplementation of Andrographis paniculata at 1.5% DM intake was able to increase milk production (FCM 3.5%), milk antioxidant content and decrease saturated fatty acid in milk of both Jamnapari and Saanen goat.